DISPARITAS DAN SPESIALISASI INDUSTRI MANUFAKTUR KABUPATEN / KOTA DI JAWA TENGAH - Kusumantoro, - (JEJAK: Jurnal Ekonomi dan Kebijakan, 2009)
The aim of this research is measure disparity and identification of specialization industry in the localregion of central java province. This research use the local government data from BPS (Badan PusatStatistik) from 2001 until 2006. Analizis of this research is index theil and regional specialization Index.The result of manufacture industry disparity in local government central java province show different levelin the Theil entropy index. Identification result of local industry in the central java province show thatindustry activity is food industry (ISIC 15), garment Industry (ISIC 17), Manufacture industry (ISIC 20)and chemical industry (ISIC 24). The specialization in the same area, usualy have the same industry.Semarang region (Semarang and kudus) is specilized in garment industry (ISIC 18) and publiser (ISIC22). Surakarta region (Sukoharjo and Karanganyar) is textile, garment and chemical specializationindustry (ISIC 24)Keywords: disparity, industry specialized, Index Theil.